Regulation of Glutamate Release by α7 Nicotinic Receptors: Differential Role in Methamphetamine-Induced Damage to Dopaminergic and Serotonergic Terminals - Northrop, Nicole A. (The American Society for Pharmacology and Experimental Therapeutics, 2011)
Regulation of glutamate release is an important underlying mechanism in mediating excitotoxic events such as damage to dopamine (DA) and serotonin (5-HT) neurons observed after exposure to methamphetamine (Meth). One way to regulate glutamate release may be through the modulation of α7 nicotinic acetylcholine (nACh) receptors. Meth administration is known to increase acetylcholine release; however, it is unknown whether Meth increases glutamate release and causes long-term damage to both DA and 5-HT terminals through the activation of α7 nACh receptors. To test this hypothesis, the α7 nACh receptor antagonist, methyllycaconitine (MLA), was administered before the administration of repeated doses of Meth while simultaneously monitoring extracellular striatal glutamate with in vivo microdialysis. In addition, the subsequent long-term decreases in markers of dopaminergic and serotonergic terminals, including DA reuptake transporter (DAT), serotonin reuptake transporter (SERT), vesicular monoamine transporter-2, vesicular DA, and vesicular 5-HT content in the rat striatum, were measured. The results show that MLA pretreatment prevented Meth-induced increases in striatal glutamate and protected against the subsequent long-term decreases in striatal DAT and vesicular DA content without affecting the hyperthermia produced by Meth. In contrast, the Meth-induced decreases in striatal SERT immunoreactivity and vesicular 5-HT content were not affected by MLA. This suggests that the α7 nACh receptor differentially mediates glutamate-dependent damage to DA but not 5-HT terminals in a manner that is independent of hyperthermia. Furthermore, antagonism of α7 nACh receptors may be a possible therapeutic strategy for decreasing extracellular glutamate and preventing the excitotoxic damage observed in other DA-related neurodegenerative disorders.